2012
DOI: 10.1113/jphysiol.2011.226878
|View full text |Cite
|
Sign up to set email alerts
|

The photovoltage of rods and cones in the dark‐adapted mouse retina

Abstract: Key points• The mouse retina has become a key model for research on the function and dysfunction of the early stages of vision, but its photoreceptors have proven difficult to access with whole-cell recording techniques.• We have optimized the mouse retinal slice preparation to the degree required for studying photoreceptors with a reasonably high yield.• We find that single photon processing in rods is considerably more efficient than previously thought, implying a more favourable transmission at the rod-rod … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
83
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(90 citation statements)
references
References 70 publications
5
83
2
Order By: Relevance
“…This is strong evidence for the presence of rod input in cones.
10.7554/eLife.01386.004Figure 2.Cones express a rod-like sensitivity to dim flashes and slow recovery after bright flashes.( A1 ) Response of a patched rod to the kinetics protocol (Figure 1C) in the first minutes after establishing the seal (black traces). At later times, a previously described rundown of kinetics was observed (gray traces; see Cangiano et al, 2012). ( A2 ) Loose seal recording showing a scaled version of the rod photovoltage in response to the kinetics protocol.
…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…This is strong evidence for the presence of rod input in cones.
10.7554/eLife.01386.004Figure 2.Cones express a rod-like sensitivity to dim flashes and slow recovery after bright flashes.( A1 ) Response of a patched rod to the kinetics protocol (Figure 1C) in the first minutes after establishing the seal (black traces). At later times, a previously described rundown of kinetics was observed (gray traces; see Cangiano et al, 2012). ( A2 ) Loose seal recording showing a scaled version of the rod photovoltage in response to the kinetics protocol.
…”
Section: Resultsmentioning
confidence: 57%
“…At later times, a previously described rundown of kinetics was observed (gray traces; see Cangiano et al, 2012). ( A2 ) Loose seal recording showing a scaled version of the rod photovoltage in response to the kinetics protocol.…”
Section: Resultsmentioning
confidence: 57%
“…Physiological and structural analysis in wild-type (wt) retinas previously demonstrated that cone photoreceptors are functionally coupled to rods [14], [15], [19][22]. This coupling is mediated by the gap junction protein connexin36 (Cx36) expressed on the cone side [11], [12], [14] and another, yet unknown connexin on the rod side.…”
Section: Resultsmentioning
confidence: 99%
“…Electrical coupling between rod and cone photoreceptors is the basic premise of the bystander hypothesis and has been demonstrated in a variety of animal models [44], including the mouse [14], [15], [19], [22], [45]. Although for the mouse only the connexin on the cone side is known (Cx36) [12], [13], several studies show that disruption of Cx36 is sufficient to disrupt rod-cone coupling [14][16].…”
Section: Discussionmentioning
confidence: 99%
“…Due to their small size and complex biochemical machinery, mouse photoreceptors (and thus, in all likelihood, mammalian photoreceptors in general) are easily perturbed by the very same electrophysiological technique that is used to record from them: our lab has recently voiced this issue, showing that perforated patch recordings of mouse rods and cones can affect membrane potentials and flash response kinetics (Cangiano et al . ), as well as rod–cone coupling (Asteriti et al . ).…”
mentioning
confidence: 99%